2015
DOI: 10.7182/pit2015415
|View full text |Cite
|
Sign up to set email alerts
|

Applying Best Practices to Designing Patient Education for Patients with End-Stage Renal Disease Pursuing Kidney Transplant

Abstract: Despite the known benefits of kidney transplant, less than 30% of the 615000 patients living with end-stage renal disease (ESRD) in the United States have received a transplant. More than 100000 people are presently on the transplant waiting list. Although the shortage of kidneys for transplant remains a critical factor in explaining lower transplant rates, another important and modifiable factor is patients’ lack of comprehensive education about transplant. The purpose of this article is to provide an overvie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 69 publications
4
50
0
Order By: Relevance
“…Previous studies have shown an association between higher transplant knowledge and better access to transplant. 12,3033 If iChoose Kidney was used in a large population (eg, among all patients in a transplant center or for a longer period of time), an increase in knowledge has the potential to lead to an improvement in transplant access. In addition, administering iChoose Kidney among ESRD patients at dialysis facilities, where patients may be less likely aware of transplantation, would possibly have a greater impact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown an association between higher transplant knowledge and better access to transplant. 12,3033 If iChoose Kidney was used in a large population (eg, among all patients in a transplant center or for a longer period of time), an increase in knowledge has the potential to lead to an improvement in transplant access. In addition, administering iChoose Kidney among ESRD patients at dialysis facilities, where patients may be less likely aware of transplantation, would possibly have a greater impact.…”
Section: Discussionmentioning
confidence: 99%
“…Administering more comprehensive transplant education and materials in varying formats, 40 such as easy-to-understand written materials or culturally competent videos with patient stories could further improve ESRD patients’ ability to make an informed decision about their treatment options. 12 …”
Section: Discussionmentioning
confidence: 99%
“…The MTC app resulted in statistically and clinically significant increases in patient knowledge The need for effective educational interventions in patients with ESRD is crucial as patients must choose between dramatically different renal replacement therapy options, especially given the ongoing and profound disparities in access to transplantation [22][23][24][25]. Patients with reduced access to specialty care and health information (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 139 patients participated in the survey. As per the results, the patients showed a positive attitude and behavior towards mobile healthcare applications (Skelton et al, 2015). Israni et al (2016) have investigated whether the use of mobile application enhances the patient adherence rate or not.…”
Section: Literature Reviewmentioning
confidence: 86%
“…Mobile applications are proving to be helpful in monitoring the kidney symptoms among patients at an early stage. A survey was conducted on the patients receiving treatment for kidney transplant by Skelton et al (2015). A total of 139 patients participated in the survey.…”
Section: Literature Reviewmentioning
confidence: 99%